Sphericity and Shape Analysis for Grain Scale Organization at Lepoh River, Hulu Langat Selangor - Mohammed, A.F.M. (Institute of Electrical and Electronics Engineers Inc., 2021)
River flow has the ability to scour the beds, carry particles and deposit these particles, forever altering their own channels. As the grain is not preserved probably, they will become non-porous or impermeable. Water will straight away run off into the river, increase the water discharge and flood may occur. Increased erosion in the upper reaches of the catchment can affect the river environment many meters downstream. Â© 2021 IEEE.